Tantangan TV lokal di era disrupsi media - Romadlono, Nanang Yulianto; Indainanto, Yofiendi Indah (Islamic Communication Journal, 2020)
Television broadcasting media during the Disruption Era was the biggest challenge for Television, especially local television to innovate and be creative in the era of technological development. Competition between the media is very tight coupled with the current Covid 19 pandemic, requiring media companies to survive in the competition of competitors. Cakra Semarang TV as Local TV in Central Java in an effort to compete in the Age of Media Disruption. The method used in this research is interpretive qualitative, using the theory of Sociocultural Evolution and Socio-technical System Theory that is used to see Cakra Semarang TV survive the media disturbances. the findings of the research show that creativity, promotional content and news as well as the application of media are the benefits that are utilized by Cakra Semarang TV to stay afloat. The application of Media Divergence by Cakra Semarang TV is a solution to the change in the way viewers watch the previously conventional Cakra Semarang TV program, but now viewers can enjoy Cakra Television Semarang TV broadcasts boldly or online. Efforts to save Cakra Semarang TV in a program broadcasting broadcast programs with the concept of divergence using YouTube streaming, social media to the site portal to get closer to the audience. This effort was carried out by Cakra Semarang TV as a way to maintain existence in the Local Television Media industry in Central Java in the Era of Disruption Current media.